Exploring Factors of Students’ Speaking Anxiety during Dialog Practice At SMPN 3 Masbagik in the Academic Year of 2025-2026 - Ratnawati; Agustina, Yulia; Nazri, M. Adib; Prasetyaningrum, Ari (PROJECT (Professional Journal of English Education), 2026)
This study aims to explore the factors contributing to students’ speaking anxiety during English dialog practice in the eighth grade of SMPN 3 Masbagik in the academic year 2025-2026. A descriptive qualitative design was employed, using observation, interviews, and questionnaires as the main instruments of data collection. The findings revealed that students experienced two types of anxiety: state anxiety and trait anxiety. State anxiety appeared in specific classroom situations, particularly when students were asked to perform dialog practice, with symptoms such as trembling hands, shaky voices, forgetting lines, and excessive sweating. Meanwhile, trait anxiety was more consistent and related to limited vocabulary, grammatical inaccuracy, and lack of confidence. The main factors that triggered speaking anxiety included limited vocabulary, fear of making mistakes, pronunciation difficulties, and fear of negative evaluation. To cope with these challenges, students applied several strategies such as repeated practice, relaxation techniques, positive self-talk, preparing vocabulary/grammar, and seeking peer support. The study concludes that students’ speaking anxiety is a multidimensional issue influenced by both linguistic and psychological factors, requiring efforts from both teachers and students to foster a more supportive learning environment.